Development of wrench-based system for occlusal force analysis: a biomechanical approach to evaluate dental occlusion - Ittetsu Uchigasaki; Yoshinori Hattori (BMC Oral Health)
Abstract Background The forces of the jaw muscles are transmitted to the dentition and the temporomandibular joints (TMJs). Imbalances in the force distribution can lead to occlusal trauma, excessive tooth wear, or TMJ osteoarthritis, making the assessment of bite force (BF) distribution clinically significant. Existing thin-film BF measurement devices capture the magnitudes of a system of BFs distributed at multiple occlusal contacts (OCs), but fail to capture their directional components, limiting their clinical utility. This study aimed to develop a method for representing BF systems as a wrench, a simplified force-couple model, using digital dentistry tools and to evaluate its reliability in terms of interexaminer reproducibility. Methods A semi-automated system was developed to integrate thin-film BF measurement data with digital models of maxillary and mandibular dental arches. BF systems were represented as wrenches with six parameters: force magnitude, axis location (x, y), axis orientation (frontal, sagittal), and pitch (moment-to-force ratio).Ten young adult participants (5 women, 5 men; mean age: 20.1 ± 2.9 years) were recruited. BF measurements were performed on all participants using the developed system. Two independent examiners manually assigned BFs to the identified OCs separately, and the reliability of these assignments was evaluated based on inter-examiner agreement. Intraclass correlation coefficients (ICCs) for wrench parameters were calculated to assess the consistency of biomechanical outcomes using appropriate statistical tests, with significance set at p < 0.05. Results The proposed system allowed substantial automation, and the manual steps were limited to segmenting the interocclusal record model for each mandibular tooth and assigning BFs to the identified OCs. The interexaminer agreement was evaluated for the BFs assigned to the identified OCs, which yielded an 87% match rate. Furthermore, the impact on wrench parameters was assessed using ICCs, which ranged from 0.93 to 0.99, indicating high reliability. Conclusions The developed system efficiently integrates BF measurements and three-dimensional OC analysis, providing a practical method for clinical evaluation of the BF systems. In addition, the system provided consistent outcomes in biomechanical analyses across different examiners.